2020
DOI: 10.1146/annurev-micro-020518-115943
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic di-AMP Signaling in Bacteria

Abstract: The second messenger molecule cyclic di-AMP (c-di-AMP) is formed by many bacteria and archaea. In many species that produce c-di-AMP, this second messenger is essential for viability on rich medium. Recent research has demonstrated that c-di-AMP binds to a large number of proteins and riboswitches, which are often involved in potassium and osmotic homeostasis. c-di-AMP becomes dispensable if the bacteria are cultivated on minimal media with low concentrations of osmotically active compounds. Thus, the essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(167 citation statements)
references
References 129 publications
5
148
0
4
Order By: Relevance
“…Based on a variety of distinct suppressor screens to adapt a B. subtilis strain lacking c-di-AMP to either the presence of glutamate or to growth on complex medium, we can conclude that the control of potassium homeostasis is the major bottleneck that limits growth of the mutant under both conditions. This is in good agreement with (i) the large variety of c-di-AMP target proteins and RNA molecules that are involved in the uptake and export of potassium in B. subtilis and other bacteria [11,13,20,21,23,31,34,45,78], (ii) the fact that the intracellular c-di-AMP levels seem to report the extracellular potassium concentrations [18,21,37], and the isolation of suppressor mutants affecting potassium homeostasis in response to altered cellular c-di-AMP levels also in other bacteria [18,37]. However, our study also clearly demonstrates that potassium is not the only problem for growth of B. subtilis in the absence of c-di-AMP since the presence of mutations that reduce potassium uptake or facilitate its export is not sufficient to overcome the toxicity of glutamate or complex medium.…”
Section: Aima (Ybec) Is a Novel Major Glutamate Transportersupporting
confidence: 81%
“…Based on a variety of distinct suppressor screens to adapt a B. subtilis strain lacking c-di-AMP to either the presence of glutamate or to growth on complex medium, we can conclude that the control of potassium homeostasis is the major bottleneck that limits growth of the mutant under both conditions. This is in good agreement with (i) the large variety of c-di-AMP target proteins and RNA molecules that are involved in the uptake and export of potassium in B. subtilis and other bacteria [11,13,20,21,23,31,34,45,78], (ii) the fact that the intracellular c-di-AMP levels seem to report the extracellular potassium concentrations [18,21,37], and the isolation of suppressor mutants affecting potassium homeostasis in response to altered cellular c-di-AMP levels also in other bacteria [18,37]. However, our study also clearly demonstrates that potassium is not the only problem for growth of B. subtilis in the absence of c-di-AMP since the presence of mutations that reduce potassium uptake or facilitate its export is not sufficient to overcome the toxicity of glutamate or complex medium.…”
Section: Aima (Ybec) Is a Novel Major Glutamate Transportersupporting
confidence: 81%
“…For many moonlighting enzymes, the signals controlling the secondary function of the enzymes have been identified (Commichau and Stülke, 2008). However, this is not the case for GlmM, which controls the activity of CdaA and thus the uptake of osmolytes via transporters whose activities are regulated by c-di-AMP (Stülke and Krüger, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…So how does a cell synthesizing CdaA and GlmM sense osmotic up-and downshifts and how is c-di-AMP production regulated by employing the phosphoglucosamine mutase? Over the past years, it has been observed that in many bacteria cdi-AMP is controlling the uptake and efflux of potassium ions to adjust the cellular turgor (Stülke and Krüger, 2020). Thus, the cellular potassium concentration could control the regulatory interaction between GlmM and CdaA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations